The Terms of Address Used by Local People “Krama Desa Adat” in Lemukih Village - Gusanto, Athanasia; Budasi, I Gede; Dewi, Kadek Sintya (Universitas Pahlawan Tuanku Tambusai, 2025)
This study explores the use of terms of address by local people (Krama Desa Adat) in Lemukih village, Buleleng Regency, Bali. The research identifies the types, functions, and social factors influencing these terms of address. Employing a descriptive qualitative approach, data were collected through observations, interviews, and recordings, then analyzed using the Huberman Data Analysis Model (Miles and Huberman, 1994). The study revealed 27 distinct terms of address used by the local community, categorized into personal pronouns, kinship terms, first names, power and hierarchy, and mockery terms. Each term serves unique functions, such as attracting attention, showing politeness and behavior, indicating power and hierarchy, reflecting identity, or expressing intimacy. For example, terms like Bape (Father) and Mbok (Sister) signify politeness, while Bayan and Nyarik denote power and hierarchy. The study also highlights six social factors influencing their use: gender, age, cultural norms, power and hierarchy, context/setting, and social status. These terms are deeply rooted in cultural values and reflect the intricate relationship between language, social structure, and community interactions. The findings emphasize the unique linguistic characteristics of Lemukih village and the need for preserving its local dialect, especially as younger generations increasingly shift to using Indonesian. This research provides significant insights into the sociolinguistic dynamics of Lemukih village and contributes to the broader understanding of linguistic diversity and cultural preservation in Bali.